Diffuse pleural thickening and thoracic contraction: An indistinguishable case from malignant pleural mesothelioma. (August 2020) - Tada, Yuji; Tagawa, Masatoshi; Yusa, Toshikazu; Yatomi, Mari; Shimomura, Iwao; Suzuki, Toshio; Takeshita, Yuichiro; Sato, Tetsuo; Shimada, Hideaki; Hiroshima, Kenzo
The differential diagnosis of reactive mesothelial hyperplasia and mesothelioma is difficult. We present a rare case of diffuse pleural thickening with thoracic contraction that was indistinguishable from mesothelioma. A 66-year-old woman with no history of asbestos exposure visited our hospital with a complaint of dyspnea. The clinical findings included circumferential pleural thickening on chest computed tomography image and a high concentration of hyaluronic acid in the pleural fluid. Pleural biopsies obtained by thoracoscopy under local anesthesia were pathologically consistent with mesothelioma, but the patient refused to take any kind of mesothelioma treatments. Four months later, she consented to a surgical pleural biopsy under general anesthesia to obtain larger tissue samples, which included typical proliferating polygonal cells positive for CAM5.2, calretinin, WT-1, D2-40, CK5/6, epithelial membrane antigen, and glucose transporter-1 and negative for carcinoembryonic antigen, BerEP4, and MOC31. The analysis was consistent with diagnosis of epithelioid mesothelioma. Fluorescence in situ hybridization, however, showed the presence of p16 gene, and the expression of BRCA1-associated protein-1 was detected by immunohistochemistry. Our final diagnosis was diffuse pleural thickening unrelated to asbestos exposure. Differential diagnosis of diffuse pleural thickening and malignant mesothelioma is thus difficult and routine immunohistochemical examinations are often insufficient for accurate diagnosis. Multiple diagnostic methods are required for correct diagnosis in a clinically marginal case.